Whole-genome sequencing reveals genetic diversity, population structure, and core collection construction in Korean peach (Prunus persica) germplasm - Bae, Seon-Hwa; Jeong, Namhee; Kwon, Jung Hyun; Lee, Ju-Hyun; Hwang, Kidong; Hur, Youn Young; Lee, So Jin (Frontiers in Plant Science, 2025)
Peach (Prunus persica) is an important temperate fruit crop and a model species for genomic research due to its diploid genome, short juvenile period, and relatively small genome size. Despite advances in next-generation sequencing (NGS), most peach genome-wide studies focused on a limited number of elite cultivars, and thus, the diversity of conserved germplasm is underrepresented. In Korea, a large number of peach genetic resources are maintained at the National Institute of Horticultural and Herbal Science (NIHHS), a branch of the Rural Development Administration (RDA), but no genome-scale core collection has been developed to date. This study aimed to perform whole-genome sequencing (WGS) on 445 peach accessions conserved in Korea between 2020 and 2025 using the Illumina NovaSeq 6000 platform, with the primary objective of constructing a representative genome-scale core collection and secondary objectives of identifying genome-wide single-nucleotide polymorphisms (SNPs) and assessing genetic diversity, population structure, and phylogenetic relationships. A total of 944,670 high-confidence SNPs were identified, with chromosomes 2 (G2) and 4 (G4) showing the highest variant density. Analyses using fastSTRUCTURE, principal component analysis (PCA), and phylogenetic reconstruction revealed a complex population structure and substantial genetic variation. From this data, a representative core collection was established, effectively capturing the majority of the genetic diversity present in the Korean peach germplasm. These results offer valuable genomic resources for peach improvement, marker development, pan-genome construction, and comparative genomics within the Rosaceae family.